Kužna slika v cerkvi Sv. Primoža nad Kamnikom in ikonografija kombinirane intercesije v času okrog 1500 - Vignjević, Tomislav (Annales. Series historia et sociologia, 2022)
In this paper, the so-called Plague Image, a celebrated mural dating to the early Slovenian Renaissance period painted on the northern wall of the Church of St. Primus above Kamnik, is carefully analysed and contextualised within the iconography of this type of image in the area of southern Germany. A comparison of this work with related art from around the year 1500 shows evidence of the dependence and connection of the St. Primus’ fresco to similar depictions of combined intercession or plague images in Central Europe, as the iconography of St. Primus’ combined intercession is quite consistent with numerous contemporary representations of this iconographic motif in southern Germany. Essentially, it is a portrayal of a double intercession by the Virgin of Mercy and the Man of Sorrows seeking to intercede with God the Father and avert the consequences of his ire from believers who, at the time of the creation of the artwork, were being plagued by wars, depredation, pestilence, famine, locusts and other adversities. The frequent perception and interpretation of the latter as apocalyptic portents further exacerbated people’s anxieties. Since such plague images, very common in the late Gothic period and the Renaissance, are visual renditions of the typical eschatological mentality of that time, this superb work of art from the Church of St. Primus is also a very telling historical document.
Keywords: Affresco dei flagelli di Dio; dipinti parietali; early Renaissance; Kužna slika; plague image; primo Rinascimento; stensko slikarstvo; Sv. Primož nad Kaminkom; wall painting; zgodnja renesansa